Hunan Valin & Arcelormittal in partnership : dancing with dragons - Williamson, Peter J., (SAGE knowledge. Cases., 2016)
This case explores how the Chinese company, Hunan Valin Steel, used overseas acquisitions and a partnership with the world's largest steel producer, Arcelor Mittal, to improve competitiveness and strategically re-position itself in the context of consolidation in the Chinese steel industry.